OPPOSITE MODULATION OF ASTROGLIAL PROLIFERATION BY ADENOSINE 5 '-O-(2-THIO)-DIPHOSPHATE AND 2-METHYLTHIOADENOSINE-5 '-DIPHOSPHATE: MECHANISMS INVOLVED - Quintas, C (2011)
The contribution of P2Y(12,13) receptors to astroglial proliferation was investigated by testing the effects of two agonists with high affinity for these receptors, adenosine 5'-O-(2-thio)-diphosphate (ADP beta S) and 2-methylthioadenosine-5'-diphosphate (2-MeSADP), in the incorporation of [H-3]-thymidine. The effect of ATP, an endogenous inducer of astroglial proliferation, was also investigated. ADP beta S and ATP (0.01-1 mM) increased astroglial proliferation up to 282%, an effect inhibited by the P2Y(1) receptor antagonist MRS 2179 (30 mu M). The P2Y(12) receptor antagonists MRS 2395 (10 mu M) and AR-C 66096 (10 mu M) also reduced ADP beta S proliferative effect, whereas the effect of ATP was attenuated by the A(2A) and A(2B) receptor antagonists SCH 58261 (30 nM) and MRS 1706 (10 nM), respectively. Studies of the signalling pathway activated showed that ADP beta S effect was attenuated by pertussis toxin and by inhibition of phopholipase C (PLC), protein kinase C (PKC) and extracellular signal-regulated kinase1/2 (ERK1/2). The effect of ATP was also attenuated by inhibition of protein kinase A (PKA). The agonist 2-MeSADP (0.001-10 mu M) had no effect in astroglial proliferation, but at higher concentrations (0.1-1 mM) it inhibited up to 63%, by mechanisms independent of P2Y(1,12,13) receptors activation. It was metabolised into 2-methylthioadenosine (2-MeSADO), the metabolite responsible for inhibition of astroglial proliferation. The effect of 2-MeSADO (0.1 mM) was attenuated by the A(3) receptors antagonist MRS 1523 (10 mu M) and by the inhibitor of nucleoside transporters uridine (0.3 mM). 2-MeSADO did not induce apoptosis but increased lactate dehydrogenase release, an indicator of necrotic cell death. Astroglial proliferation induced by ADP beta S was mediated by P2Y(1) and P2Y(12) receptors, leading to activation of PLC-PKC-ERK1/2 signalling pathway. The ATP proliferative effect was also mediated by PKA, supporting the contribution of the A(2) receptors. 2-MeSADP inhibition of astroglial proliferation depended on its conversion into 2-MeSADO, which activated A(3) receptors, blocked [H-3]-thymidine uptake by astrocytes and led to cell death.